An Exploration of Color Linguistics: Fundamental Concepts and Terminological Approaches (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the terminology and conceptualization of color in linguistics, focusing on the terms "coloronim" and "chromatonym." The paper also addresses the use of terms like "linguo-color picture" and its equivalents in other languages, reflecting modern anthropocentric linguistics. A key issue is the lack of a unified system for studying color-denoting lexical units in Uzbek linguistics, despite the existence of over two hundred such units, including adjectives, converted nouns, metaphors, adverbs, onomatopoeia, and compound terms. The authors propose using "color names" or "color lexicon" in a broad sense, and "color-denoting lexical units" or "coloronims" in a narrow sense, as generalizing terms. The "linguo-color picture of the world" or "colorful linguistic picture of the world" are also proposed. The paper then analyzes the lexeme "rang" (color) in the "Explanatory Dictionary of the Uzbek Language," examining its seven distinct meanings and the semantic components associated with each, ranging from "substance used for painting" to "the specific color of something."